Qualidade vocal de professores do magistério superior de uma universidade pública em Belém do Pará - ASSUNÇÃO, José Antonio Mendes de (2019)
Introduction: The estimated prevalence of voice disorders among the general population ranges from 6% to 15%. However, when it comes to teachers, these values range from 20% to 50%, up to 80%. This has a negative impact on the quality of life of voice professionals, consequently, it generates direct or indirect damages on social and professional life. Objective: This study aimed to evaluate the voice quality of teachers at a public university in Belém do Pará, analyzing their prevalence, risk factors, vocal self - knowledge, preventive measures and verifying the presence of institutional promotions of voice care. Theoretical reference: The Occupational Dysphonic Syndrome (ODS) describes functional dysphonia in voice professionals, among them, the group most affected is the teachers. The main complaints reported by these professionals are "dry throat", hoarseness and vocal fatigue. The main risk factors for ODS are organizational work process and individual. Method: A cross - sectional and descriptive epidemiological survey was carried out. A total of 103 teachers from the Federal University of Pará participated through a research protocol. The Chi-square test was used to correlate the data. Results: We observed the prevalence of males and mean age of 48 years. In the study, more than 50% of the teachers were overweight or obese, 28.16% had more than five clinical symptoms related to voice, the most prevalent being laryngopharyngeal pain or irritation (54.9%). When we correlated some data with the symptoms, only the water intake presented statistical relevance, the other analyzed variables did not have significant difference. Conclusion: The results presented by this study show that most teachers of the research have good voice quality, with less than five clinical symptoms, even those with poor life habits and little voice care.